2005
DOI: 10.2337/diabetes.54.12.3592
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hypoglycemia-Associated Autonomic Failure and Its Component Syndromes in Diabetes

Abstract: Iatrogenic hypoglycemia is a problem for people with diabetes. It causes recurrent morbidity, and sometimes death, as well as a vicious cycle of recurrent hypoglycemia, precluding maintenance of euglycemia over a lifetime of diabetes. Improved therapeutic approaches that will minimize both hypo-and hyperglycemia will be based on insight into the pathophysiology of glucoregulation, specifically glucose counterregulation, in insulin-deficient (type 1 and advanced type 2) diabetes. In such patients, hypoglycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
263
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 347 publications
(281 citation statements)
references
References 138 publications
(121 reference statements)
10
263
0
8
Order By: Relevance
“…Recurrent episodes of hypoglycaemia may result in hypoglycaemia unawareness [5]. Large population-based studies have shown that despite efforts to improve treatment of type 1 diabetes, hypoglycaemia remains a problem [2,5] and there is need for strategies that will minimise episodes of severe hypoglycaemia. On the other hand, a majority of patients never experience a hypoglycaemic coma or convulsion [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent episodes of hypoglycaemia may result in hypoglycaemia unawareness [5]. Large population-based studies have shown that despite efforts to improve treatment of type 1 diabetes, hypoglycaemia remains a problem [2,5] and there is need for strategies that will minimise episodes of severe hypoglycaemia. On the other hand, a majority of patients never experience a hypoglycaemic coma or convulsion [2].…”
Section: Introductionmentioning
confidence: 99%
“…While the fundamental alteration could be in the afferent or efferent components of the sympathoadrenal system, it is often assumed to reside within the central nervous system. Potential mechanisms, mostly focused on the hypothalamus, have been reviewed (11,12).…”
mentioning
confidence: 99%
“…While the fundamental alteration could be in the afferent or efferent components of the sympathoadrenal system, it is often assumed to reside within the central nervous system. Potential mechanisms, mostly focused on the hypothalamus, have been reviewed (11,12).Measurements of the increase from baseline in regional cerebral blood flow with [15 O]water and positron emission tomography (PET) can be used to identify regions of increased brain synaptic activity and to determine which brain regions are involved with different physiological CBF, cerebral blood flow; HAAF, hypoglycemia-associated autonomic failure; PET, positron emission tomography; PVNT, paraventricular nucleus of the thalamus. …”
mentioning
confidence: 99%
“…Predictive validity, which is necessary for pharmacologic or interventional testing, can be the most difficult to achieve and has not yet been demonstrated for HAAF. Construct validity examines the theoretical rationale of the model for congruence to the clinical problem; both human studies and rodent HAAF models are being pursued in parallel to test several hypothesized mechanisms of HAAF (as reviewed in Cryer, 2005). Reliability of models is also important to establish but may be difficult to assess between laboratories if the model is relatively new, as with the HAAF models, or if any experimental practices vary widely.…”
Section: Resultsmentioning
confidence: 99%